Analysis of Learning Media Needs for Economics in the Digital Era at SMA Muhammadiyah 1 Sekampung Udik - Wulandari, Herma; Dewi, Tiara Anggia; Sholiha, Sangidatus (Economic Education and Entrepreneurship Journal, 2024)
The digital era has brought significant changes to the field of education, particularly in the use of technology as a learning medium. The utilization of digital-based learning media has become essential to meet the needs of the current generation, which tends to be more interactive and independent. This study aims to analyze the needs for economics learning media in the digital era to enhance students' understanding and engagement in the learning process. The research employed a qualitative descriptive method with data collection techniques, including observations, interviews, and questionnaires. The subjects of the study involved 79 tenth-grade students and teachers of economics at SMA Muhammadiyah 1 Sekampung Udik. The results revealed that the majority of students faced difficulties in understanding economics material, with 55.7% stating that learning economics was moderately difficult and 39.2% finding it very difficult. Most students (62%) expressed a strong need for additional learning media, particularly audio-visual-based media, while 44.3% were highly interested in Android-based learning media. Furthermore, the study highlights that the majority of students experience challenges in comprehending economics concepts, indicating a significant demand for digital-based learning media. Audio-visual and Android-based learning media are considered effective in improving flexibility, independence, and students' understanding of complex economic concepts. Therefore, the adoption of interactive and adaptive digital technology-based learning media is a strategic step to support the effectiveness of economics learning in the global era.DOI: http://dx.doi.org/10.23960/E3J/v7.i2.165-174